Metabolomics and network pharmacology exploration of the effects of bile acids on carotid atherosclerosis and potential underlying mechanisms - Cheng, Xing; Zhang, Ruijing; Qi, Xiaotong; Wang, Heng; Gao, Tingting; Zheng, Lin; Qiao, Maolin; Li, Yaling; Gao, Siqi; Chen, Jinshan; Chang, Runze; Zheng, Guoping; et al. (Frontiers in Endocrinology, 2024)
Background: Bile acids (BAs), products of gut microbiota metabolism, have long been implicated in atherosclerotic disease pathogenesis. Characterizing the serum bile acid profile and exploring its potential role in carotid atherosclerosis (CAS) development are crucial tasks.In this study, we recruited 73 patients with CAS as the disease group and 77 healthy individuals as the control group. We systematically measured the serum concentrations of 15 bile acids using ultrahigh-performance liquid chromatography-mass spectrometry (UPLC-MS/MS).Multivariate logistic regression and least absolute shrinkage and selection operator (LASSO) regression were applied to analyze the impact of bile acids on the disease and select the key BAs. The possible molecular mechanism was elucidated by network pharmacology.(1) The BA profile of patients with CAS significantly differed. (2) Multifactorial logistic regression analysis identified elevated levels of GCDCA (OR: 1.01, P < 0.001), DCA (OR: 1.01, P = 0.005), and TDCA (OR: 1.05, P = 0.002) as independent risk factors for CAS development.Conversely, GCA (OR: 0.99, P = 0.020), LCA (OR: 0.83, P = 0.002), and GUDCA (OR: 0.99, P = 0.003) were associated with protective effects against the disease. GCA, DCA, LCA, and TDCA were identified as the four key BAs. (3) TNF, FXR, GPBAR1, ESR1 and ACE were predicted to be targets of BAs against AS. These four BAs potentially impact AS progression by triggering signaling pathways, including cAMP, PPAR, and PI3K-AKT pathways, via their targets.This study offers valuable insights into potential therapeutic strategies for atherosclerosis that target bile acids.